Numerical Mathematics and Advanced Applications 2011 Proceedings of ENUMATH 2011, the 9th European Conference on Numerical Mathematics and Advanced Applications, Leicester, September 2011 - Cangiani, Andrea; Davidchack, Ruslan L.; Georgoulis, Emmanuil; Gorban, Alexander N.; Levesley, Jeremy; Tretyakov, Michael V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The European Conferences on Numerical Mathematics and Advanced Applications (ENUMATH) are a series of conferences held every two years to provide a forum for discussion of new trends in numerical mathematics and challenging scientific and industrial applications at the highest level of international expertise. ENUMATH 2011 was hosted by the University of Leicester (UK) from the 5th to 9th September 2011. This proceedings volume contains more than 90 papers by speakers of the conference and gives an overview of recent developments in scientific computing, numerical analysis, and practical use of modern numerical techniques and algorithms in various applications. New results on finite element methods, multiscale methods, numerical linear algebra, and finite difference schemes are presented. A range of applications include computational problems from fluid dynamics, materials, image processing, and molecular dynamics.
Part I A Posteriori Error Estimation and Adaptive Methods -- Part II Computational Electromagnetics -- Part III Computational Methods -- Part IV Convection, Diffusion, Conservation, and Hyperbolic Systems -- Part V Discontinuous Galerkin Methods -- Part VI Finite Element and Finite Volume techniques -- Part VII Fluid Mechanics -- Part VIII High Performance Computing -- Part IX Multiscale Modeling and Simulations -- Part X Preconditioners and Solvers -- Part XI Uncertainty, Stochastic Modelling, and Applications.
Keywords: Mathematics; Computer science -- Mathematics; Computer science; Numerical analysis; Mathematics; Computational Mathematics and Numerical Analysis; Applications of Mathematics; Numerical Analysis; Computational Science and Engineering; Mathematical Modeling and Industrial Mathematics; Theoretical, Mathematical and Computational Physics